Anatomical constraints to nonstomatal diffusion conductance and photosynthesis in lycophytes and bryophytes. Issue 3 (3rd February 2019) - Carriquí, Marc; Roig‐Oliver, Margalida; Brodribb, Timothy J.; Coopman, Rafael; Gill, Warwick; Mark, Kristiina; Niinemets, Ülo; Perera‐Castro, Alicia V.; Ribas‐Carbó, Miquel; Sack, Lawren; Tosens, Tiina; Waite, Mashuri; et al.
Summary: Photosynthesis in bryophytes and lycophytes has received less attention than terrestrial plant groups. In particular, few studies have addressed the nonstomatal diffusion conductance to CO2 g nsd of these plant groups. Their lower photosynthetic rate per leaf mass area at any given nitrogen concentration compared with vascular plants suggested a stronger limitation by CO2 diffusion. We hypothesized that bryophyte and lycophyte photosynthesis is largely limited by low g nsd . Here, we studied CO2 diffusion inside the photosynthetic tissues and its relationships with photosynthesis and anatomical parameters in bryophyte and lycophyte species in Antarctica, Australia, Estonia, Hawaii and Spain. On average, lycophytes and, specially, bryophytes had the lowest photosynthetic rates and nonstomatal diffusion conductance reported for terrestrial plants. These low values are related to their very thick cell walls and their low exposure of chloroplasts to cell perimeter. We conclude that the reason why bryophytes lie at the lower end of the leaf economics spectrum is their strong nonstomatal diffusion conductance limitation to photosynthesis, which is driven by their specific anatomical characteristics.